The logic behind negotiation : from pre-argument reasoning to argument-based negotiation - Brito, Luís (2003)
The use of agents in Electronic Commerce environments leads to the necessity to introduce some formal analysis and definitions. A 4-step method is introduced for developing EC-directed agents, which are able to take into account non-linearites such as gratitude and agreement. Negotiations that take into account a multi-step exchange of arguments provide extra information, at each step, for the intervening agents, enabling them to react accordingly. This argument-based negotiation among agents has much to gain from the use of Extended Logic Programming mechanisms. Incomplete information is common in EC scenarios; therefore arguments must also take into account the presence of statements with an unknown valuation.